2004
DOI: 10.1002/neu.20075
|View full text |Cite
|
Sign up to set email alerts
|

Growth cones turn and migrate up an immobilized gradient of the laminin IKVAV peptide

Abstract: Growth cone navigation is guided by extrinsic environmental proteins, called guidance cues. Many in vitro studies have characterized growth cone turning up and down gradients of soluble guidance cues. Although previous studies have shown that axonal elongation rates can be regulated by gradients of surface-bound molecules, there are no convincing demonstrations of growth cones turning to migrate up a surface-bound gradient of an adhesive ligand or guidance cue. In order to test this mode of axonal guidance, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
118
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(122 citation statements)
references
References 63 publications
3
118
1
Order By: Relevance
“…Disruption of axon-substrate attachment in vitro with integrin function-blocking antibodies encourages axon-axon adhesive interactions (fasciculation) in place of axon-substrate adhesion (Bozyczko and Horwitz, 1986). Furthermore, contact with integrin ligands can slow axon elongation, as axons encountering an increasing gradient of laminin peptide exhibit reduced velocity, but growth cone velocity returns to previous rates when axons turn down the gradient (Adams et al, 2005). This in vitro observation resembles in vivo situations in which growth cones slow at a choice point, exhibit increased morphological complexity and then extend along distinct pathways (Godement et al, 1994;Gomez and Spitzer, 1999;Tosney and Landmesser, 1985).…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Disruption of axon-substrate attachment in vitro with integrin function-blocking antibodies encourages axon-axon adhesive interactions (fasciculation) in place of axon-substrate adhesion (Bozyczko and Horwitz, 1986). Furthermore, contact with integrin ligands can slow axon elongation, as axons encountering an increasing gradient of laminin peptide exhibit reduced velocity, but growth cone velocity returns to previous rates when axons turn down the gradient (Adams et al, 2005). This in vitro observation resembles in vivo situations in which growth cones slow at a choice point, exhibit increased morphological complexity and then extend along distinct pathways (Godement et al, 1994;Gomez and Spitzer, 1999;Tosney and Landmesser, 1985).…”
Section: Research Articlementioning
confidence: 99%
“…Genetic analyses in C. elegans, Drosophila and mice reveal that axon extension in integrin mutants in vivo is not compromised during development; however, defects in axon guidance result from loss of integrin function (Baum and Garriga, 1997;Billuart et al, 2001;Hoang and Chiba, 1998;Pietri et al, 2004;Stevens and Jacobs, 2002). In combination with in vitro and in vivo observations addressing the effects integrins and their ligands exert on growing axons (Adams et al, 2005;Bonner and O'Connor, 2001;Garcia-Alonso et al, 1996;Gomez et al, 1996;Hopker et al, 1999;Kuhn et al, 1995), these studies define functions for integrin signaling in guiding growing axons, strongly suggesting that integrins are essential for axon guidance.…”
Section: Introductionmentioning
confidence: 99%
“…Functionality of these peptides has been assessed in various applications. Adams et al showed that DRG neurons, that were grown on gradients of photoimmobilized IKVAV bound polystyrene grids, preferentially directed their neurites toward higher concentration of IKVAV containing surface (Adams et al 2005 ). In another study, melt coextruded aligned poly(ε-caprolactone) (PCL) fi bers were modifi ed with photochemical gradient of IKVAV peptide, which provided directional cues for neuronal outgrowth of PC-12 cells (Kim et al 2015 ).…”
Section: Surface Chemistry and Biochemical Modifi Cations To Increasementioning
confidence: 99%
“…The integrin-binding activity of natural adhesion proteins can be partially mimicked by oligopepetide sequences [95,96], such as the ubiquitous RGD (i.e., arginineglycine-aspartic acid) [97][98][99][100], RGD and PHSRN (i.e., proline-histidine-serine-arginineasparagine) (in synergy) [101,102], IKVAV (i.e., isoleucine-lysine-valine-alanine-valine) [103][104][105], YIGSR (tyrosine-isoleucine-glycine-serine-arginine) [106,107], PHSRN , and so on. Harden et al went a step further from the triblock architecture initially proposed by Tirrell et al by conjugating RGD to the central block of the modular triblock protein architecture.…”
Section: Artificial Protein Hydrogelsmentioning
confidence: 99%